Meningkatkatkan Kecerdasan Spiritual Melalui Bermain Peran Penelitian Tindakan di KB & TK Bunga Bangsa Islamic School Bekasi - Wahyuni Nadar (STIT Al-Marhalah Al-Ulya Bekasi, 2017)
In general, the purpose of this study is to obtain data about the spiritual intelligence of children aged 5-6 years in the center of al Islam KB TK Bunga Bangsa Islamic School through role play. This research was conducted at KB TK Bunga Bangsa Islamic School Bekasi which is located on Jl. Kh. Agus Salim Number 206, Kelurahan Margahayu, District of East Bekasi, Kota Bekasi, West Java Province. Specifically this research will see how big role play can improve every aspect that exist in spiritual intelligence for children aged 5-6 years at KB TK Bunga Bangsa Islamic School Bekasi. This research was conducted in second semester of academic year 2016/2017. This action study was conducted using a cycle model from Stephen Kemmis and Mc Taggart. Action research is carried out through planning, implementation, observation and reflection. This research was conducted in two cycles and started with pre-research activities. The average praintervensi result is 57%, in cycle 1 the result is 65,5% and cycle 2 reaches 80% on average. From the data there is a significant increase in each cycle. Improvement is seen in every aspect that depicts children's spiritual intelligence such as self-awareness, spontaneity, internally motivated, seeing life from vision and based on fundamental, holistic values, seeing system and universality, compassion (sense of community, sense of following the flow of life) diversity, independent, firm against the majority, fundamentally questioning, rearranging in the big picture, and steadfast in difficulty.Thus, the learning process through the role play to improve spiritual intelligence is said to have been achieved because most of the indicators in the competence of the ability of spiritual intelligence has increased. The implication of this research is that role playing can be one strategy to improve spiritual intelligence.